Dataset for "Mass loss of the Antarctic ice sheet until the year 3000 under a sustained late-21st-century climate" - Chambers, Christopher; Greve, Ralf; Obase, Takashi; Saito, Fuyuki; Abe-Ouchi, Ayako (Zenodo, 2022)
Dataset for the paper "Mass loss of the Antarctic ice sheet until the year 3000 under a sustained late-21st-century climate" (Journal of Glaciology, https://doi.org/10.1017/jog.2021.124). Please see the README for details. V2: New version with ISMIP6-type variables and compressed netCDF files. V1: Initial upload. * * * * * * * The following script may be used to download the entire content of the archive on a Unix/Linux system: #!/bin/bash # --- download_all.sh --- wget https://zenodo.org/record/6215117/files/_README.pdf wget https://zenodo.org/record/6215117/files/run_specs_headers.zip for aexp in hist ctrl_proj_long \ exp05_long exp06_long exp07_long exp08_long exp09_long exp10_long \ exp12_long exp13_long \ expA5_long expA6_long expA7_long expA8_long \ expB6_long expB7_long expB8_long expB9_long expB10_long; do wget https://zenodo.org/record/6215117/files/${aexp}.zip done for aexp in abuc_long abuciso_long \ abuk_long abukiso_long \ abum_long abumiso_long; do wget https://zenodo.org/record/6215117/files/${aexp}.zip done * * * * * * * Users should cite the original publication when using all or parts of these data. : Funding acknowledgements: Christopher Chambers, Ralf Greve and Ayako Abe-Ouchi were supported by Japan Society for the Promotion of Science (JSPS) KAKENHI Grant No. JP17H06323. Ralf Greve and Ayako Abe-Ouchi were supported by JSPS KAKENHI Grant No. JP17H06104. Takashi Obase, Fuyuki Saito and Ayako Abe-Ouchi were supported by JSPS Grant-in-Aid for Japan--France Integrated Action Program (SAKURA Program) No. JPJSBP120213203.